Core-shell flaky WSe2 / S3Se5-coated PANI composite material as well as preparation method and application thereof
By functionalizing the sulfur to modify WSe2 and coated PANI nanofibers, a core-shell sheet-like WSe2/S3Se5@PANI composite material is formed, which solves the problems of low sensitivity, poor selectivity and poor moisture resistance of the sensor, and achieves high sensitivity, fast response and good selectivity of the ammonia sensor performance.
Patent Information
- Application Number
- CN202510687509.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-27
- Publication Date
- 2025-08-15
AI Technical Summary
Existing ammonia sensors have problems such as low sensitivity, slow response speed, poor selectivity and poor humidity resistance, especially in high humidity environments, which significantly reduce their performance.
By functionalizing the flaky WSe2, a WSe2/S3Se5 structure is formed, and the surface is coated with PANI nanofibers to form a core-shell flaky WSe2/S3Se5@PANI composite material. The conductivity of PANI and the weak binding ability to water molecules are used to improve electron transport ability and selectivity, and enhance the response to ammonia.
It realizes high sensitivity detection of ammonia at room temperature, responds quickly and recovers quickly, has good selectivity, and maintains a high response rate in a high humidity environment, significantly improving the humidity resistance of the sensor.
Smart Images

Figure CN120490233A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensor technology, and in particular to a core-shell flaky WSe2 / S3Se5@PANI composite material and a preparation method and application thereof. Background Art
[0002] Ammonia is a common organic gas, but its excessive release can cause air pollution and health risks. Currently, common ammonia sensors suffer from low sensitivity, slow response speed, poor selectivity, and poor moisture resistance. Tungsten diselenide (WSe2) can be used as an active material for gas sensors due to its high surface sensitivity, high surface-to-volume ratio, and excellent electrical properties. For example, existing literature 1 (Yujuan Hu, Kelin Hu, Jing Zhang, Yuxiao Jiang, et al. WSe2 modified monocrystalline SnSe2 nanosheets for hydrogen gas detection and its sensing mechanism [J]. International Journal of Hydrogen Energy, 2024) developed a WSe2-based hydrogen gas sensor. Although the sensor exhibited good selectivity for hydrogen at 270°C, achieving a high response rate of 727% at 100 ppm hydrogen, the original WSe2 material had insufficient surface active site density and weak adsorption energy with target gas molecules, resulting in low effective charge transfer efficiency and, consequently, low sensitivity.
[0003] Therefore, in order to solve the problem of low sensitivity of the sensor, a heterojunction can be constructed by loading a compound to improve the sensitivity of the composite material. For example, existing document 2 (Preeti Shakya, Mohammed Saquib Khan, Sanjay Kumar, Deependra Jhankal, et al. Room-Temperature 2H-WSe2 / rGO Composite based NO2Gas Sensor with Long-Term Stability[J]. IEEE Sensors Journal, 2025.) discloses a WSe2 / rGO composite material with a layered structure, which accelerates charge transfer and enhances gas-sensitive performance by constructing a pp heterostructure. Although this technical solution achieves the effect of improving gas-sensitive performance under conditions of low operating temperature, it has the advantage that the surface active sites of WSe2 not only have a high affinity for NO2, but also have a certain adsorption effect on other gas molecules, that is, the technical solution does not have selectivity. The direct consequence is that in a complex detection environment, WSe2 will adsorb multiple gas molecules at the same time, and the purpose of detection cannot be achieved.
[0004] For the problem of low selectivity, it can be improved by sulfur functionalization modification. For example, existing document 3 (XuTian, Xiuxiu Cui, et al.Ultrasensitive room-temperature flexible ammonia gassensor based on Au-functionalized polypyrrole wrapped enriched edge sulfurvacancies MoS2 nanosheets[J].Sensors and Actuators B:Chemical, 2023.) discloses a kind of resistive gas sensor based on Au / MoS2 / PPy composite material, uses simple liquid phase ultrasonic stripping process to combine in situ polymerization method to prepare composite material, Au loads on MoS2 and PPy form a good conductive network for charge transfer between, and the sensor obtained shows good selectivity to ammonia. Although this technical solution is realized under the conditions of room temperature, the effect of higher selectivity is obtained, but the material after sulfurization is prone to strong interaction with water molecules in the air, resulting in the adsorption of water molecules on active sites, competing with ammonia molecules for adsorption sites, and then there is a problem of poor moisture resistance.
[0005] In response to the problem of poor moisture resistance, it can be improved by compounding with a conductive polymer. For example, existing literature 4 (Runze Zhang, Bin Wang, Xiaolin Wang, et al. A fast response NH3 gas sensor based on phthalocyanine-optimized non-covalent hybrid of polypyrrole [J]. Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2024.) prepared an ammonia sensor based on PPy / 4-fPoPcCo nanocomposite material, and tested the response of the sensor under different humidity conditions (10%, 30%, 50%, 70% and 90% RH). The test results show that the response rate of the sensor is basically the same under a relative humidity environment of 0%-54.4%, which is mainly attributed to the surface modification of PPy by 4-fPoPcCo, the large specific surface area and porous structure provided by the nanofibrous structure, and the π-π interaction between PPy and 4-fPoPcCo that promotes electron transport. These factors work together to enable the sensor to maintain stable sensing performance under high humidity conditions. However, the sensor's response value decreases under conditions of relative humidity exceeding 60%, indicating that it is not moisture-resistant under high humidity conditions. The reason is that its nanostructure aggregates and collapses due to water penetration, resulting in a significant reduction in effective active sites, thereby reducing the sensor's response performance.
[0006] Similarly, there are existing technologies with poor moisture resistance, as well as the previous research results of the research group of the present invention. In the existing document 5 (CN116380988A, a MXene / MoS2 / polypyrrole composite material and its preparation method and application), PPy is used to in-situ polymerize and coat the MXene / MoS2 composite material. This technical solution successfully improved the response rate of the MXene / MoS2 composite material to NH3 through PPy coating. However, according to subsequent studies, the use of PPy as a coating layer also has the problem of poor moisture resistance. The reason is that the fast protonation process of PPy leads to poor moisture resistance, which makes the composite material have a low response rate in a high humidity environment. Summary of the Invention
[0007] The purpose of the present invention is to provide a core-shell flaky WSe2 / S3Se5@PANI composite material and its preparation method and application.
[0008] In the existing technology, the sheet-like structure of WSe2 is calcined and sulfurized to obtain the sheet-like structure of WSe2 / S3Se5. The sulfur functionalization modification enhances the electron transport ability of WSe2, accelerates the carrier migration rate, and improves the gas sensing performance. Subsequently, PANI is in situ polymerized and coated on the surface of the sheet-like structure of WSe2 / S3Se5, effectively increasing the moisture resistance of the gas sensor. The specific functions of each component are:
[0009] 1. Calcination of WSe2 using sulfur functionalization modification effectively reduces the interference of other gases on ammonia through the sulfur-containing acidic functional groups, that is, improves the selectivity for ammonia. At the same time, due to the highly selective adsorption and strong interaction of WSe2 / S3Se5 with ammonia molecules, it can produce detectable signals at lower ammonia concentrations, with a lower detection limit;
[0010] 2. Using PANI as the coating layer has three functions:
[0011] 2.1. PANI, as a conductive polymer, provides additional conductive pathways, thereby improving the overall conductivity of the material;
[0012] 2.2. Due to the protonation / deprotonation process of the conductive polymer itself when in contact with ammonia, the response to ammonia is improved;
[0013] 2.3. The surface of the PANI coating is smooth and has weak binding ability to water molecules. A water film layer can be formed on the PANI surface. The thickness of the water film layer increases with the increase of humidity. At the same time, when ammonia molecules interact with the water film, the water molecule film falls off quickly. At the same time, ammonia molecules are adsorbed by PANI, thereby reducing the effect of humidity and hindering the reaction of NH3 with the composite material, which essentially changes the moisture resistance of the material.
[0014] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0015] A core-shell sheet-like WSe2 / S3Se5@PANI composite material is obtained by compounding sheet-like WSe2 / S3Se5 and PANI nanofibers, wherein:
[0016] WSe2 / S3Se5 is in flake form with a size of 3-5 μm. WSe2 / S3Se5 is obtained by sulfurization treatment of WSe2.
[0017] PANI nanofibers are evenly coated on the surface of WSe2 / S3Se5. After being coated with PANI, they still maintain a sheet-like structure with a size of 3-5μm.
[0018] A method for preparing a core-shell flaky WSe2 / S3Se5@PANI composite material comprises the following steps:
[0019] Step 1, preparation of WSe2 / S3Se5, placing sulfur powder upstream and WSe2 downstream, calcining under certain conditions to achieve sulfurization treatment, and then obtaining WSe2 / S3Se5 with a flake structure;
[0020] In step 1, the calcination conditions are: under argon gas conditions, the calcination temperature is 350°C, the calcination time is 1-3 hours, and the mass ratio of sulfur powder to WSe2 is 6:1;
[0021] Step 2, PANI coating, the WSe2 / S3Se5 obtained in step 1 is placed in HCl and mixed and stirred to obtain a mixed solution, and ammonium persulfate is pre-cooled in an ice-water mixture. Then, aniline and ammonium persulfate are added to the mixed solution in sequence under stirring conditions to obtain a reaction solution. Finally, under stirring conditions, the reaction solution is polymerized under certain conditions to obtain a core-shell sheet-like WSe2 / S3Se5@PANI composite material, referred to as WSe2 / S3Se5@PANI;
[0022] In step 2, the mass ratio of WSe2 / S3Se5 and aniline is 20:47;
[0023] In step 2, the mixing and stirring conditions are as follows: the stirring time is 30 minutes;
[0024] In the step 2, the polymerization conditions are as follows: the polymerization temperature is 0-5° C. and the polymerization time is 6 hours.
[0025] A WSe2 / S3Se5@PANI-based sensor has a response rate of 500-600% to 100 ppm NH3 at room temperature and a humidity of 45%. The response time is 440-450 seconds, the recovery time is 480-490 seconds, and the detection limit is 180-190 ppb.
[0026] In the presence of NO2, CO2, H2, H2S, CH4 and NH3, it is selective for NH3;
[0027] Under the condition of humidity of 0-90%, it has the response rate to NH3, that is, it has moisture resistance;
[0028] Under the condition of 90% humidity, the response rate of NH3 reaches 800-900%.
[0029] The technical effects of the present invention have been tested and the specific contents are as follows:
[0030] XRD test of WSe2 / S3Se5@PANI composite material showed that WSe2 / S3Se5@PANI contained the characteristic peaks of WSe2, S3Se5 and PANI at the same time.
[0031] EDS testing of the WSe2 / S3Se5@PANI composite material showed that the WSe2 / S3Se5@PANI core-shell sheet structure contained not only the W and Se elements of WSe2 and the S element of WSe2 / S3Se5, but also the N element of PANI.
[0032] SEM testing of WSe2 / S3Se5@PANI composite material showed that WSe2 / S3Se5@PANI has a core-shell flake structure, PANI is coated on the surface of the flake WSe2 / S3Se5@PANI composite material, and the composite material also has a flake structure with a size of 3-5μm.
[0033] The WSe2 / S3Se5@PANI composite material has the best gas sensing performance test.
[0034] The ammonia concentration pulse test of the WSe2 / S3Se5@PANI sensor showed that under the specific test conditions of temperature of 25°C and humidity of 45%, ammonia of known concentration was introduced into the gas chamber for ammonia concentration detection experiment. The detection limit based on the WSe2 / S3Se5@PANI sensor was 180-190ppb; and the following conclusion can be drawn: the introduction of PANI can significantly reduce the baseline resistance of the sensor and greatly improve the response rate to NH3.
[0035] The response-recovery performance test of the WSe2 / S3Se5@PANI sensor showed that the response time was 440-450s and the recovery time was 480-490s, that is, the WSe2 / S3Se5@PANI-based sensor has the characteristics of relatively fast response and recovery.
[0036] Humidity testing of the WSe2 / S3Se5@PANI sensor showed that it can efficiently detect ammonia gas over a wide humidity range of 0%-90%. Furthermore, at a humidity of 90%, the sensor's response rate reached 800-900%. These test results demonstrate the WSe2 / S3Se5@PANI sensor's ability to operate in high-humidity environments.
[0037] Selectivity testing of the WSe2 / S3Se5@PANI sensor showed that at room temperature, the sensor's response to 100 ppm of NH3, NO2, CO2, H2, H2S, and CH4 was 550-560%, significantly higher than that of the other gases. These results demonstrate the WSe2 / S3Se5@PANI sensor's selectivity for ammonia.
[0038] According to the above test results, the present invention has the following advantages over the prior art:
[0039] 1. The present invention performs sulfur functionalization modification on the sheet-like structure of WSe2 to increase its electron transport ability, accelerate the migration rate of carriers, and thus improve the gas sensing performance.
[0040] 2. The present invention can control the micromorphology of the composite material by adjusting the synthesis ratio. The obtained core-shell flaky WSe2 / S3Se5@PANI composite material has a flaky structure composed of WSe2 / S3Se5. WSe2 / S3Se5 helps improve the gas-sensing performance of the material by providing sulfur-containing acidic functional groups and highly selective adsorption of ammonia molecules.
[0041] 3. In the core-shell flaky WSe2 / S3Se5@PANI composite material of the present invention, the PANI coating layer has a smooth surface and weak binding ability to water molecules. When ammonia molecules interact with this water film, the water molecule film is quickly detached. At the same time, the ammonia molecules are adsorbed by the PANI, reducing the effect of humidity hindering the reaction of NH3 with the composite material, greatly improving the moisture resistance of the material, and changing the previous response rate decrease in high humidity environments to the response rate increase in high humidity environments;
[0042] 4. The core-shell sheet WSe2 / S3Se5@PANI-based NH3 gas sensor of the present invention can quantitatively test the ammonia concentration. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is the XRD spectrum of WSe2 / S3Se5@PANI-20 in Example 1;
[0044] Figure 2 This is the EDS graph of WSe2 / S3Se5 in Example 1;
[0045] Figure 3 is the SEM image of WSe2 / S3Se5 in Example 1;
[0046] Figure 4 The resistance change curve of WSe2 / S3Se5 to ammonia concentration in Example 1;
[0047] Figure 5 The response rate change curve of WSe2 / S3Se5 to ammonia concentration in Example 1;
[0048] Figure 6 This is the EDS spectrum of WSe2 / S3Se5@PANI-20 in Example 1;
[0049] Figure 7 This is the SEM image of WSe2 / S3Se5@PANI-20 in Example 1;
[0050] Figure 8 The resistance change curve of WSe2 / S3Se5@PANI-20 to ammonia concentration in Example 1;
[0051] Figure 9 This is the response rate change curve of WSe2 / S3Se5@PANII-20 to ammonia concentration in Example 1;
[0052] Figure 10 This is the recovery time curve of WSe2 / S3Se5@PANI-20 response to ammonia in Example 1;
[0053] Figure 11 The effect of humidity on the ammonia response rate of WSe2 / S3Se5@PANI-20 in Example 1;
[0054] Figure 12 The selectivity of WSe2 / S3Se5@PANI-20 to ammonia and other gases in Example 1;
[0055] Figure 13 The figure is a comparison chart of the response rates of Example 1, Comparative Example 1 and Comparative Example 2 to different concentrations of ammonia. DETAILED DESCRIPTION
[0056] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0057] Example 1
[0058] A method for preparing a core-shell flaky WSe2 / S3Se5@PANI composite material comprises the following steps:
[0059] Step 1, preparation of WSe2 / S3Se5, placing sulfur powder upstream and WSe2 downstream, calcining under certain conditions to achieve sulfurization treatment, and then obtaining WSe2 / S3Se5 with a flake structure;
[0060] In the step 1, the calcination conditions are: under argon gas conditions, the calcination temperature is 350° C., the calcination time is 1-3 hours, and the mass ratio of sulfur powder to WSe2 is 6:1.
[0061] In order to prove the composition of WSe2 / S3Se5, XRD test and EDS test were performed.
[0062] XRD test results are as follows Figure 1 As shown, the diffraction peaks of WSe2 and S3Se5 exist simultaneously in WSe2 / S3Se.
[0063] EDS test results are as follows Figure 2As shown, WSe2 / S3Se5 contains W, Se and S elements at the same time.
[0064] In order to verify the microstructure of WSe2 / S3Se5, SEM test was carried out. The test results are as follows Figure 3 As shown, WSe2 / S3Se5 is a flake structure with a size of 3-5μm.
[0065] In order to demonstrate the performance of WSe2 / S3Se5 as the active material of ammonia sensor, that is, the performance of WSe2 / S3Se5 sensor in detecting NH3, a WSe2 / S3Se5-based sensor was prepared, and gas concentration detection experiments were carried out.
[0066] The preparation method of the gas sensor is as follows: first, 6 mg of active material and 1 mL of anhydrous ethanol are mixed and ground to obtain a mixed solution; then, 20 μL of the mixed solution is dropped onto the surface of a gold interdigital electrode and spin-coated; finally, the gold interdigital electrode is connected to the gas chamber to obtain a gas sensor based on the active material, namely a gas-sensitive test system.
[0067] The gas concentration detection experiment, a performance test method for a gas sensor, involves passing a test gas of a certain concentration into the gas chamber under certain test temperature and test humidity conditions. The resistance of the gas sensor is then measured, and the response rate is calculated. Unless otherwise specified, the test temperature is 25°C, the test humidity is 45%, the test gas is ammonia, and the test gas concentration is 10-100ppm.
[0068] The ammonia concentration detection experimental test results of the WSe2 / S3Se5 sensor are shown in Table 1. Figure 4 and Figure 5 As shown in Figure 3, the WSe2 / S3Se5 sensor has a high resistance value and a low response rate. The test results show that the conductivity and gas sensing performance of the WSe2 / S3Se5 sensor are poor.
[0069] Table 1 Changes in resistance and response rate of WSe2 / S3Se5 sensor to different concentrations of ammonia at room temperature
[0070] Ammonia concentration (ppm) Resistance (MΩ) Response rate (%) 0 0 0 10 191.71 45.81 20 223.7 70.21 30 262.4 99.52 40 284.23 116.24 50 336.14 155.68 100 394.95 200.74
[0071] Step 2, PANI coating, 200 mg of WSe2 / S3Se5 obtained in step 1 is placed in 60 mL of 0.5 M HCl, and the mixture is stirred for 30 min to obtain a mixed solution. At the same time, ammonium persulfate is pre-cooled in an ice-water mixture. Then, under stirring conditions, 466 μL of aniline and 571 mg of ammonium persulfate are added to the mixed solution in sequence to obtain a reaction solution. Finally, under stirring conditions, the reaction solution is polymerized at a polymerization temperature of 3°C and a polymerization time of 6 h to obtain a core-shell sheet-like WSe2 / S3Se5@PANI composite material, abbreviated as WSe2 / S3Se5@PANI-20.
[0072] In order to prove the composition of WSe2 / S3Se5@PANI-20, XRD test and EDS test were performed.
[0073] XRD test results are as follows Figure 1 As shown, WSe2 / S3Se5@PANI-20 contains the characteristic peaks of WSe2, S3Se5 and PANI.
[0074] EDS test results are as follows Figure 6 As shown in the figure, WSe2 / S3Se5@PANI-20 presents a core-shell sheet structure with WSe2 / S3Se5 as the core and PANI as the shell. In addition to the W and Se elements of WSe2 and the S element of WSe2 / S3Se5, there is also the N element of PANI.
[0075] The combination of XRD and EDS tests not only proves that WSe2 / S3Se5@PANI-20 was successfully prepared in step 2, but also proves that PANI was successfully coated on the surface of the WSe2 / S3Se5 sheet structure through step 2.
[0076] In order to prove the micromorphology of WSe2 / S3Se5@PANI-20, that is, the effect of PANI coating on the micromorphology, SEM test was carried out. The test results are as follows Figure 7 As shown, PANI is coated on the surface of the WSe2 / S3Se5 sheet structure, and the composite material also presents a sheet structure with a size of 3-5μm.
[0077] In order to demonstrate the performance of WSe2 / S3Se5@PANI-20 as the active material of ammonia sensor, that is, the detection performance of NH3 based on WSe2 / S3Se5@PANI sensor, a WSe2 / S3Se5-based sensor was prepared, and gas concentration detection experiments were carried out.
[0078] The ammonia concentration detection experimental test results of WSe2 / S3Se5@PANI-20 sensor are shown in Table 2. Figure 8 and Figure 9Compared with the WSe2 / S3Se5 sensor obtained in step 1, the introduction of PANI can significantly reduce the baseline resistance of the sensor and greatly improve the response rate to NH3. The reasons are reflected in the following four aspects:
[0079] 1. PANI, as a conductive polymer, provides additional conductive pathways, thereby improving the overall conductivity of the material;
[0080] 2. When exposed to NH3, the electronic structure of PANI undergoes significant changes, thereby changing the charge carrier density and mobility;
[0081] 3. The π-conjugated structure of PANI interacts with the layered structure of WSe2 / S3Se5, which can promote interfacial charge transfer;
[0082] 4. The doping state of PANI (e.g., protonation) can further regulate the band structure of the material and optimize its sensitivity and selectivity to NH3;
[0083] Based on the above reasons, the introduction of PANI not only reduces the baseline resistance of the sensor, but also improves the sensitivity of the sensor to NH3.
[0084] Table 2 Changes in resistance and response rate of WSe2 / S3Se5@PANI-20 sensor to different concentrations of ammonia at room temperature
[0085] Ammonia concentration (ppm) Resistance (KΩ) Response rate (%) 0 0 0 10 517.15 133.01 20 696.76 214.5 30 836.53 276.5 40 965.96 334.75 50 1086.9 389.13 100 1344.81 505.6
[0086] In order to further prove the performance of the gas sensor based on WSe2 / S3Se5@PANI-20 sensor, a response-recovery test was performed. The test results are shown in Figure 2. Figure 10 As shown in the figure, the response time is 443.62s and the recovery time is 481.45s. The test results show that the WSe2 / S3Se5@PANI-based sensor has the characteristics of fast response and recovery.
[0087] In order to demonstrate the effect of humidity on the WSe2 / S3Se5@PANI-20 sensor, a humidity test was conducted. The other test conditions were kept the same, except that the test was conducted in a humidity range of 0-90%. The test results are shown in Table 3 and Figure 11 As shown in the figure, the WSe2 / S3Se5@PANI-20 sensor can efficiently detect ammonia in a wide humidity range of 0%-90%, and the sensor response rate is as high as 857.68% under the condition of 90% humidity. The test results show that the WSe2 / S3Se5@PANI-20 sensor has the performance to work in high humidity environment.
[0088] The reasons are reflected in the following two aspects:
[0089] 1. Under high humidity conditions, a large number of water molecules adsorbed on the surface of the WSe2 / S3Se5@PANI-20 sensor form a water molecule film. When encountering NH3 molecules, the surface tension of the water molecule film is destroyed, and a large number of water molecules are desorbed, which weakens the protonation degree of PANI and causes the resistance value of the sensor to rise rapidly.
[0090] 2. NH3 can react with water molecules on the PANI surface to generate NH4 + and OH-, the deprotonation rate of the generated OH- is greater than that of NH3, which then takes protons from the acidified PANI, further reducing the doping level of PANI, resulting in an increase in the resistance of the sensor and an increase in the response value.
[0091] Table 3 Effect of humidity on the response rate of WSe2 / S3Se5@PANI-20 sensor
[0092] humidity(%) Response rate (%) 0 186.24 25 229.35 50 378.84 75 673.33 90 857.68
[0093] In order to prove the selectivity of the WSe2 / S3Se5@PANI-20 sensor for ammonia, a gas concentration detection experiment was conducted. The other test conditions were kept the same, except that the test gases were NO2, CO2, H2, H2S, and CH4. The response rates of the WSe2 / S3Se5@PANI sensor are shown in Table 4 and Figure 12 As shown in the figure, the response rates for NH3 are 560.23%, NO2 are 41.85%, CO2 are 37.9%, H2 are 61.51%, H2S are 27.6%, and CH4 are 14.8%. The test results show that the WSe2 / S3Se5@PANI sensor is selective for ammonia.
[0094] Table 4 WSe2 / S3Se5@PANI-20 sensor selectivity test table
[0095] Gas type Response rate (%) <![CDATA[NH3]]> 560.23 <![CDATA[H2]]> 61.51 <![CDATA[NO2]]> 41.85 <![CDATA[CO2]]> 37.9 <![CDATA[H2S]]> 27.6 <![CDATA[CH4]]> 14.8
[0096] In order to demonstrate the effect of the aniline addition ratio on the performance, comparative examples 1 and 2 are provided, in which the aniline addition ratios are the mass ratios of aniline to WSe2 / S3Se5@PANI, referred to as mass ratios, of 47:40 and 47:10, respectively.
[0097] Comparative Example 1
[0098] A WSe2 / S3Se5@PANI composite material with a mass ratio of 47:40, wherein the steps not specifically described are the same as those in Example 1, except that in step 2, the amount of aniline added is 233 μL, and the obtained material is named WSe2 / S3Se5@PANI-40.
[0099] The ammonia concentration test results of WSe2 / S3Se5@PANI-40 are shown in Table 5 and Figure 13 As shown in the figure, the response rate of WSe2 / S3Se5@PANI-40 to 100 ppm ammonia at room temperature is 348.37%, which is 68.91% of the response rate of WSe2 / S3Se5@PANI-20 to ammonia under the same conditions. This is because the low amount of PANI added fails to completely cover WSe2 / S3Se5@PANI, resulting in WSe2 / S3Se5@PANI playing a major role in the gas-sensing performance, resulting in a lower response rate to ammonia.
[0100] Comparative Example 2
[0101] A WSe2 / S3Se5@PANI composite material having a mass ratio of aniline to WSe2 / S3Se5@PANI of 47:10, wherein the steps not specifically described are the same as those in Example 1, except that the amount of aniline added in step 3 is 698.475 μL, and the obtained material is named WSe2 / S3Se5@PANI-10.
[0102] The ammonia concentration test results of WSe2 / S3Se5@PANI-10 are shown in Table 5 and Figure 13 As shown in the figure, the response rate of WSe2 / S3Se5@PANI-10 to 100 ppm ammonia at room temperature is 320.44%, which is 63.38% of the response rate of WSe2 / S3Se5@PANI-20 to ammonia under the same conditions. This is because the excessive amount of PANI added causes excessive coating of WSe2 / S3Se5@PANI, resulting in a decrease in the number of exposed active sites and a lower response rate to ammonia.
[0103] Table 5 Comparison of response rates between Example 1 and comparative example
[0104] Ammonia concentration (ppm) Example 1 Response rate (%) Comparative Example 1 Response rate (%) Comparative Example 2 Response rate (%) 0 0 0 0 10 133.01 106.57 91.59 20 214.5 162.42 142.39 30 276.5 202.47 179.04 40 334.75 237.63 212.81 50 389.13 270.42 242.59 100 505.6 348.37 320.44
[0105] By comparing Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that the addition ratio of aniline has a significant effect on the gas-sensing properties of the WSe2 / S3Se5@PANI composite material.
Claims
1. A core-shell sheet-like WSe2 / S3Se5@PANI composite material, characterized by: It is made of sheet-like WSe2 / S3Se5 and PANI nanofiber composite, among which, WSe2 / S3Se5 is in flake form with a size of 3-5 μm. WSe2 / S3Se5 is obtained by sulfurization treatment of WSe2. PANI nanofibers are evenly coated on the surface of WSe2 / S3Se5. After being coated with PANI, they still maintain a sheet-like structure with a size of 3-5μm.
2. A method for preparing a core-shell flaky WSe2 / S3Se5@PANI composite material, characterized in that The following steps are involved: Step 1, preparation of WSe2 / S3Se5, placing sulfur powder upstream and WSe2 downstream, calcining under certain conditions to achieve sulfurization treatment, and then obtaining WSe2 / S3Se5 with a flake structure; Step 2, PANI coating, the WSe2 / S3Se5 obtained in step 1 is placed in HCl and mixed and stirred to obtain a mixed solution. At the same time, ammonium persulfate is pre-cooled in an ice-water mixture. Then, aniline and ammonium persulfate are added to the mixed solution in sequence under stirring conditions to obtain a reaction solution. Finally, under stirring conditions, the reaction solution is polymerized under certain conditions to obtain a core-shell sheet-like WSe2 / S3Se5@PANI composite material, referred to as WSe2 / S3Se5@PANI.
3. The preparation method according to claim 2, wherein: In the step 1, the calcination conditions are: under argon gas conditions, the calcination temperature is 350° C., the calcination time is 1-3 hours, and the mass ratio of sulfur powder to WSe2 is 6:
1.
4. The preparation method according to claim 2, wherein: In step 2, the mass ratio of WSe2 / S3Se5 and aniline is 20:47; In step 2, the mixing and stirring conditions are as follows: the stirring time is 30 minutes; In the step 2, the polymerization conditions are as follows: the polymerization temperature is 0-5° C. and the polymerization time is 6 hours.
5. A sensor based on WSe2 / S3Se5@PANI, characterized by: Under the conditions of room temperature and humidity less than 45%, the response rate to 100ppm NH3 is 500-600%, the response time is 440-450s, the recovery time is 480-490s, and the detection limit is 180-190ppb.
6. The WSe2 / S3Se5@PANI sensor according to claim 6, characterized in that: In the presence of NO2, CO2, H2, H2S, CH4 and NH3, it is selective for NH3, with a response rate of NH3 of 550-560%.
7. The WSe2 / S3Se5@PANI sensor according to claim 6, characterized in that: Under the condition of humidity of 0-90%, it has the response rate to NH3, that is, it has moisture resistance.
8. The WSe2 / S3Se5@PANI sensor according to claim 8, characterized in that: Under the condition of 90% humidity, the response rate of NH3 reaches 800-900%.
Citation Information
Patent Citations
MXene / MoS2 / polypyrrole composite material as well as preparation method and application thereof
CN116380988A